INTENSITAS PEMBERDAYAAN PETANI DI KABUPATEN CIANJUR TAHUN 2006 - Achmad Suwandi (Politeknik Pembangunan Pertanian Bogor, 2020)
Intensity of farmer empowering in Cianjur – West Java, 2006 is a result of simpleresearch, particularly the implementation of extension activities along 2006, specifically on twocommodities (vegetables and rice). The objective of this research is the farmer in area ofCianjur district, that has grown two commodities along 2006.The result of the research indicates that activities of agricultural extension with goodenough categories are:1. Information services by specific institute, like KUD, etc (83,80%).2. The supports of farmer group (kelompok tani) in agriculture activities (69,00%) or 3,45.The aspects of agricultural extension with less categories includes:1. Daily activities by extension worker (PPL) categorized as enough (61,24%), it means thatthe intensity of visit and frequency of farmer meeting is less.2. Facilities of agricultural extension, particularly for extension workers is less, so the visit isnot running very well.